2020
DOI: 10.3389/fgene.2020.00517
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Gene Co-expression Networks in Time-Series Data: A Case Study in Drosophila melanogaster Embryogenesis

Abstract: Co-expression networks tightly coordinate the spatiotemporal patterns of gene expression unfolding during development. Due to the dynamic nature of developmental processes simply overlaying gene expression patterns onto static representations of coexpression networks may be misleading. Here, we aim to formally quantitate topological changes of co-expression networks during embryonic development using a publicly available Drosophila melanogaster transcriptome data set comprising 14 time points. We deployed a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The promise of multiomic data will remain unfulfilled without methodological approaches capable of identifying system perturbations associated with phenotypic change. Here, we used a gene regulatory network approach which has proven successful for investigation of puberty and other complex traits [ 20 , 65 , 66 ]. We identified TRIM25, a gene encoding the estrogen-responsive finger protein, as the network element undergoing the most dramatic change in connectivity and strongly suggests it plays a key role.…”
Section: Discussionmentioning
confidence: 99%
“…The promise of multiomic data will remain unfulfilled without methodological approaches capable of identifying system perturbations associated with phenotypic change. Here, we used a gene regulatory network approach which has proven successful for investigation of puberty and other complex traits [ 20 , 65 , 66 ]. We identified TRIM25, a gene encoding the estrogen-responsive finger protein, as the network element undergoing the most dramatic change in connectivity and strongly suggests it plays a key role.…”
Section: Discussionmentioning
confidence: 99%
“…A study in mice showed that animals lacking this gene rapidly succumbed to infection with influenza virus [ 34 ]. Overall, the significant changes in the gene co-expression networks between the HEALTHY and MORIBUND groups explored in this study suggest an important role of these transcription factors in the molecular events that underpin POMV infection [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A powerful approach to overcome this problem is gene co-expression network analysis [ 8 ]. Co-expression networks constructed from RNA expression data can effectively capture relationships between transcripts and reveal a biologically meaningful higher-order organization of the transcriptome [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic scans for detecting selection signatures have been successfully applied to several domestic animals, including aquaculture species. For instance, selection signature scans have been carried out for Atlantic salmon 19 24 , Nile tilapia 25 , 26 ; and channel catfish 27 . To date, there are no studies focusing on the identification of selection signatures in farmed coho salmon populations.…”
Section: Introductionmentioning
confidence: 99%